(untitled) (Research, Society and Development, 2022)
This study aimed to compare, in an interval of three months, the anthropometric measurements of children and adolescents belonging to a soccer school in the state of Paraná. Prospective study, in which 88 children and adolescents (10.85 ± 2.36 years of age) were evaluated. For anthropometric evaluation, a Sanny® brand stadiometer (height measurement) and a G-Life® brand digital scale (body mass assessment) were used. Anthropometric measurements were collected at two times: at the beginning of the study and after 90 days. Data were analyzed by multivariate analysis of variance (MANOVA), Box’s M Test, Hotelling’s Trace, analysis of variance (ANOVA) and Bonferroni adjustment (p < 0.05). The intragroup result showed that there was no change in anthropometric indicators over the three months. In the intergroup analysis, the categories differed in the variables of body mass (p = 0.001), height (p = 0.001) and BMI (p = 0.001) both in the pre- and post-test moments, with all groups showing an increase in body mass and height from pre to post-test, and three (under-11, under-13 and under-15) of the four groups showed a reduction in BMI. Athletes in the sub-13 and sub-15 categories presented higher values ​​in all variables in the two evaluated moments. It was concluded that the anthropometric measurements did not change over three months in children and adolescents who play soccer.